2015
DOI: 10.5301/ejo.5000660
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Ranibizumab for Choroidal Neovascularization Secondary to Gyrate Atrophy in a Young Patient: A Multimodal Imaging Analysis

Abstract: Intravitreal ranibizumab can offer promising anatomical and functional results, maintaining visual acuity in patients with CNV secondary to GA, especially if used in combination with arginine-restricted diet and vitamin B6 supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…1,49 Fluorescein angiography may also demonstrate leakage in cases of GA that are complicated by subretinal choroidal neovascularisation. 50,51 The evaluation of GA can be also performed and followed up using ultra-widefield imaging which has been found to allow superior imaging of the peripheral retina simultaneously with the macula. 22,52 Electroretinography (ERG) may reveal diminished a and b wave responses from both cones and rods which may become undetectable in advanced disease, 53 however, a nearly normal ERG recording in association with GA has also been previously reported following long-term follow-up.…”
Section: Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,49 Fluorescein angiography may also demonstrate leakage in cases of GA that are complicated by subretinal choroidal neovascularisation. 50,51 The evaluation of GA can be also performed and followed up using ultra-widefield imaging which has been found to allow superior imaging of the peripheral retina simultaneously with the macula. 22,52 Electroretinography (ERG) may reveal diminished a and b wave responses from both cones and rods which may become undetectable in advanced disease, 53 however, a nearly normal ERG recording in association with GA has also been previously reported following long-term follow-up.…”
Section: Investigationsmentioning
confidence: 99%
“…5,77 Pars plana vitrectomy can be performed for the treatment of macular holes, 44 rhegmatogenous retinal detachments, 78 and vitreous hemorrhage, 79 while intravitreal injection of anti-vascular endothelial growth factor agents can be used for the treatment of choroidal neovascularisation. 45,50 Finally, the use of low-vision aids may be of benefit to some patients with advanced disease, however, the diffuse chorioretinal atrophy that may be present in late disease and involves the macula as well as the retinal periphery may limit the options available for these patients. Although there is scarce information on the use of lowvision aids for patients with GA, its symptoms and unaltered natural course are similar to retinitis pigmentosa on which more studies have been performed.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 It has been reported that the combination of arginine restricted diet can improve the visual acuity of patients with choroidal neovascularization (CNV) after the intravitreal injection of ranibizumab. 36 L-arginine contributed additional effects on exercise-induced angiogenesis possibly by enhancing VEGF expression in the hind-leg muscles and heart. 37 On the other hand, the enhancement of NO synthesis pathway is characteristic of pro-inflammatory M1-like macrophages, whereas the expression of arginase characterizes M2 macrophages, and arginase hydrolyzes arginine to ornithine and urea while limiting the synthesis of NO derived from arginine.…”
Section: Discussionmentioning
confidence: 96%
“…CNV rarely develops. [132][133][134] OCTA shows perifoveal microvascular alterations and petaloid non-reflective areas in the deep capillary plexus. 135 Full field ERG shows impaired cone and rod esponses in early stages.…”
Section: Gyrate Atrophymentioning
confidence: 99%